The Power of Your Life The Sanlam Century of Insurance Empowerment, 1918-2018 - Verhoef, Grietjie (Oxford University Press, 2019)
This book explores a century of business development in The South African Life Assurance Company, from a specific local focus to a national conglomerate expanding into global insurance markets. Established as a strategic vehicle to address Afrikaner economic marginalization and abject poverty at the beginning of the twentieth century, Sanlam has displayed both path dependence and a dynamic adaptability to complex changing contexts to become a global player. The strategic convergence of economic empowerment through the mobilization of savings into insurance products, as well as Afrikaner nationalism, assisted this growth. Sanlam has played an a-typical role in the economic empowerment of an ethnic entity through extensive investments into the industrializing South African economy. This strategic diversion created operational limitations that were only resolved early in the twenty-first century. As globalization, financial deregulation, and weakened Afrikaner political and social hegemony manifested, strategic change management relied on the path dependence of empowerment strategies to address new markets with similar needs to those of the early stakeholder market of 1918. The former mutual life office demutualized operations to become a diversified financial services group of companies operating across almost the entire African continent, as well as in India, Malaysia, and the UK. This volume presents a business history of strategic management of an insurance enterprise, and its transformation from a defined cultural context into an international empowerment strategy through innovation on all levels of business operation and organization.